72.5k views
2 votes
Q4.) Solve the equation by the method of your choice.

Q4.) Solve the equation by the method of your choice.-example-1

1 Answer

3 votes
Hey there!

First, you must find the common denominator of the equation.

To find the common denominator, first take a look at all the factors of each denominator:

x: x
x+4: x+4
6: 2*3

Next, because you do not have a common multiple in the denominators, you would multiply the denominators together to create one common multiple:
6(x)(x+4). This would be used to remove the fractions from the equation to make it easier to solve.

Now, multiply the common multiple 6(x)(x+4) to the entire equation:
(6(x)(x+4)) × (
(1)/(x) +
(1)/(x+4) =
(1)/(6))

When you multiply the factor to the equation, the x in the common factor would cancel out the x in
(1)/(x) resulting in just 6(x+4).

The x+4 would cancel out the x+4 factor in
(1)/(x+4) resulting in just 6x.

The 6 would cancel out the 6 in
(1)/(6) resulting in just x(x+4).

As a result, when you multiply the common factor 6(x)(x+4) to
(1)/(x) +
(1)/(x+4) =
(1)/(6), you will get
(6(x+4))+ 6x = x(x+4)

Now, simplify the equation further:
(6(x+4))+ 6x = x(x+4)
6x+24+6x=x^2+4x (I have distributed the values in the parentheses)
12x+24=x^2 + 4x (I combined like terms on both sides)
0=x^2-8x-24 (I have moved all terms to one side so that the x values can be solved for using the quadratic formula)

Because this quadratic does not factor evenly, we must use the quadratic formula in order to find the exact x values:
x=
(-b±√(b^2-4ac) )/(2a)

Your a value is 1, your b value is -8, and your c value is -24:
x=
(-(-8) ±√((-8)^2-4(1)(-24)) )/(2(1))
x=
(8 ±√(64+96) )/(2)
x=
(8 ±√(160) )/(2)
x=
(8 ±4√(10) )/(2)
x=4±2
√(10)

Therefore, your x values are 4+2
√(10) and 4-2
√(10)


User Nick Hutchinson
by
6.4k points